Efektivitas Implementasi Kurikulum Merdeka Belajar pada Pembelajaran Bahasa Indonesia kelas II di UPT SDN Unggulan Bontomanai - Kristin Lestari Eliaser; Syamsul Alam; Siti Nurul Halizah; Nurhadifah Amaliyah (Journal on Education, 2024)
Based on initial observations carried out at UPT SDN Unggulan Bontomanai, research was conducted to find out the effectiveness, supporting factors, inhibiting factors and solutions for implementing the Independent Learning curriculum in class II Indonesian language learning at UPT SDN Unggulan Bontomanai. The type of research used in this research is descriptive qualitative. The research subject was class II UPT SDN Unggulan Bontomanai. The data collection techniques used are observation, interviews and documentation. The results obtained in implementing the independent learning curriculum in class II Indonesian language learning at UPT SDN Unggulan Bontomanai have been effective. The supporting factors are the guidance of the teacher or educator, the students themselves, the students' parents and supporting teaching materials or learning media, while the inhibiting factor is that not all students can be orderly during learning so this is certain to disturb the students. another. The teacher must provide understanding and guidance to participants about the importance of learning Indonesian and orderliness in implementing this learning, then slowly students will understand. The impact is that it has a positive impact on both teachers and students.